A Community Based Assessment of Health-Related Quality of Life in the Elderly Population of Bengaluru South - Johnson, Praisy; Lavanya, Sasubilli; Abraham, Jisin; Kishore, Githa (Indian Journal of Pharmacy Practice)
Background: Globally the quality of life (QOL) among the elderly is deteriorating. Therefore, it should be considered as an important aspect to improve their health and wellbeing. Objectives: To assess the quality of life of elderly population in Bengaluru South. Methodology: A community based cross sectional study was conducted among 400 elderly subjects residing in South of Bengaluru for a period of 6 months. Their QOL was assessed by using WHOQOL-BREF instrument. Socio-demographic factors and morbidities were collected using a specially designed questionnaire. Data was analysed using SPSS version 16. The difference between the mean scores was tested using independent sample t test and ANOVA. Results: A majority, 54.75%, of study participants were in the age group of 60-69 years. The mean scores of physical, psychological, social and environmental domains was found to be 48.60, 51.26, 48.37 and 59.66 respectively. Hypertension and vision impairment were the most prevalent ailment. The QOL was significantly lower among subjects with advancing age, with no formal education and those who were staying without a partner. Female subjects were having lower QOL than males. Those with musculoskeletal disorders and hearing impairment had significantly lower QOL. Conclusion: Ageing is something which cannot be prevented from happening, however one should overcome this through certain versatile activities like social and family support, frequent health examinations, legal security and unique schemes for elderly which helps them to improve their QOL.
Keywords: Elderly; Health-related quality of life (HRQOL); WHOQOL-BREF; Quality of life (QOL); Morbidities.